Control of Reynolds number in a high speed wind tunnel - Silva, Maurício G.; Gamarra, Victor O.r. [UNESP]; Koldaev, Vitor (Departamento de Ciência e Tecnologia Aeroespacial, 2009)
A conceptual control model for the Reynolds number test based on isentropic relations was established for the supersonic wind tunnel. Comparison of the system response of the model simulation and the actual wind tunnel test data was made to design the control system. Two controllers were defined: the first one was based on the stagnation pressure at the settling chamber; the second was based on the relation between stagnation pressure and temperature at the settling chamber which represents the Reynolds number specified for the test. A SIMULINK® block diagram code was used to solve the mathematical model consisting of mass and energy conservation equations. Performance of the supersonic wind tunnel using a PI (proportional-plus-integral) controller was found to be satisfactory, as confirmed by the results.
Keywords: Blowdown wind tunnel; Pressure control; Mach number control; Reynolds number control